Synthesis, Antifungal Activity, and Cytotoxicity of AgBr-NP@CTMAB Hybrid and Its Application in PMMA - Zhang, Qiao-Jun (Int J Nanomedicine, 2021)
OBJECTIVE: To synthesize and determine the antifungal activity of AgBr-nanoparticles (NP) @CTMAB (cetyltrimethyl-ammonium bromide) against Candida albicans (C. albicans) for use in the field of denture cleaning. METHODS: The morphology and structure of AgBr-NP@CTMAB were characterized by IR, UV-Vis, XRD and SEM. The antifungal potential of AgBr-NP@CTMAB against C. albicans was determined by colony formation assay and growth curve analysis. PMMA containing AgBr-NP@CTMAB was prepared, and the long-term antifungal efficacy was analyzed. The effect against C. albicans biofilm was analyzed by SEM and OD600 , and the color changes of the specimens were observed by stereomicroscopy after 1 week of incubation. Cytotoxicity to human oral gingival fibroblasts and oral mucosal epithelial cells was detected by Cell Counting Kit-8 (CCK-8) in vitro. RESULTS: The compound showed a good crystalline phase, the presence of AgBr nanoparticles and the hybridization of CTMAB+ with AgBr-NPs. AgBr-NP@CTMAB showed significant antifungal activity against C. albicans at concentrations of 10 μg/mL and 20 μg/mL. PMMA specimens containing AgBr-NP@CTMAB showed no long-term antifungal effect against C. albicans biofilm. The clearance rate of C. albicans attached to PMMA was 44.73% after soaking in 10 µg/mL AgBr-NP@CTMAB solution for 30 min and 91.35% for 8 h. There was no significant residual cytotoxicity or visual color change after soaking. SIGNIFICANCE: AgBr-NP@CTMAB showed promising potential treatment for denture cleaners.